The association between vitamin D intake with inflammatory and biochemical indices and mortality in critically ill patients with COVID‐19: A case‐control study - Maryam Gholamalizadeh; Faezeh Rabbani; Mina Ahmadzadeh; Azadeh Hajipour; Hayehe Musavi; Khadijeh Abbasi Mobarakeh; Zahra Salimi; Bojlul Bahar; Zahra Mahmoodi; Somayeh Gholami; Samaneh Mirzaei Dahka; Saeid Doaei; et al. (Immunity, Inflammation and Disease)
Abstract Background The coronavirus disease‐2019 (COVID‐19) has become a worldwide health issue with widespread hospitalization and dependence on the intensive care unit (ICU). Vitamin D has a key role in modulating immune cells and modulating the inflammatory responses. This study aimed to investigate the association of vitamin D supplementation with inflammatory, biochemical, and mortality indices in critically ill patients with COVID‐19. Methods This case‐control study was conducted on critically ill COVID‐19 patients hospitalized in the ICU including the survived >30 day patients as the case group and dead patients as the control group. The status of vitamin D supplementation and inflammatory and biochemical indices of the patients were retrieved from the medical records. Logistic regression method was used to assess the association between 30 days survival and vitamin D supplement intake. Results Compared to the group of COVID‐19 patients who died in <30 day, the survived patients had a lower eosinophile level (2.2 ± 0.5 vs. 6 ± 0.0, p < .001) and higher vitamin D supplementation duration (9 ± 4.4 vs. 3.3 ± 1.9 day, p = .001). Vitamin D supplementation had a positive association with survival in COVID‐19 patients (OR: 1.98, 95% CI: 1.15−3.40, p < .05). The association remained significant after adjustments fot age, sex, underlying diseases, and smoking. Conclusion Vitamin D supplementation in critically ill patients with COVID‐19 has the potential to increase survivability within the first 30 days of hospitalization.